STRATEGI GURU PAI DALAM MENINGKATKAN MINAT BELAJAR DAN PRESTASI SISWA PADA MIN 3 KOTA PALANGKA RAYA - Mustika Triani; Samsudin Samsudin; Choeroni Choeroni (JCI Publisher, 2026)
This study aims to describe the strategies of Islamic Religious Education (PAI) teachers in increasing student learning interest and achievement at MIN 3 Palangka raya City. The study used a qualitative descriptive approach with research subjects being PAI teachers, madrasah principals, and sixth-grade students. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis used the Miles and Huberman model which includes data collection, data reduction, data presentation, and drawing conclusions. The results showed that PAI teachers' strategies in increasing student learning interest were carried out through the use of varied learning methods such as discussions, questions and answers, demonstrations, direct practice, educational games, and storytelling methods. Teachers also used learning media such as videos, images, posters, and presentation slides to attract students' attention. These strategies were proven to be able to increase student interest, activeness, and motivation in learning. In addition, PAI learning strategies also improved student learning achievement in the cognitive, affective, and psychomotor aspects. Students became more understanding of the material, demonstrated better behavior, and were able to practice worship correctly. Supporting factors for the research include a religious school environment, support for learning facilities, and parental cooperation, while the obstacles faced include differences in student abilities, lack of learning motivation, and limited learning media.